2015
DOI: 10.1101/gr.188870.114
|View full text |Cite
|
Sign up to set email alerts
|

A nucleosome turnover map reveals that the stability of histone H4 Lys20 methylation depends on histone recycling in transcribed chromatin

Abstract: Nucleosome composition actively contributes to chromatin structure and accessibility. Cells have developed mechanisms to remove or recycle histones, generating a landscape of differentially aged nucleosomes. This study aimed to create a highresolution, genome-wide map of nucleosome turnover in Schizosaccharomyces pombe. The recombination-induced tag exchange (RITE) method was used to study replication-independent nucleosome turnover through the appearance of new histone H3 and the disappearance or preservation… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

9
54
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 56 publications
(63 citation statements)
references
References 77 publications
(110 reference statements)
9
54
0
Order By: Relevance
“…Exchange is even more rapid when transcription is occurring in these regions. Similar turnover studies have been conducted in flies, mice and humans, including expanded studies to monitor turnover of histone variants 6265 , as well as the turnover rates of PTMs 66 . Together, these studies have revealed that genomic regions with the highest rates of nucleosome (and histone) turnover are biochemically active.…”
Section: Nucleosome Occupancymentioning
confidence: 86%
“…Exchange is even more rapid when transcription is occurring in these regions. Similar turnover studies have been conducted in flies, mice and humans, including expanded studies to monitor turnover of histone variants 6265 , as well as the turnover rates of PTMs 66 . Together, these studies have revealed that genomic regions with the highest rates of nucleosome (and histone) turnover are biochemically active.…”
Section: Nucleosome Occupancymentioning
confidence: 86%
“…Histone modifications serve the role of allotting the genome into "active" or euchromatin, in which DNA is accessible for transcription, and "inactive" or heterochromatin, in which DNA is inaccessible for transcription [94]. Histones are characterized by their large number and diversity of modified residues [95].…”
Section: Histone Modifications and Their Biological Rolesmentioning
confidence: 99%
“…H3K9 methylation decreased after the release of the methyltransferase in the wild type but was maintained across generations and postmeiosis in a deletion mutant of the lysine demethylase Epe1 . Peter Svensson (Karolinska Institute, Sweden) described the genomewide nucleosome turnover based on the recombination-induced tag exchange (RITE) method adapted for S. pombe in collaboration with Allshire's group; accordingly, he showed low and high nucleosome turnover in heterochromatin and high-expression chromatin regions, respectively (Svensson et al 2015). Shiv Grewal (National Institutes of Health, USA) presented findings from his group's genomewide chromatin conformation capture (Hi-C) analysis (Mizuguchi et al 2014).…”
Section: Topicsmentioning
confidence: 99%